Effects of PCNL under the guidance of hologram technology on stress response and renal injury factors in patients with complex kidney stones: PCNL with Hologram Tech: Impact on Kidney Stone Patients - Liu, Changming; Dong, Zimin; Sheng, Mingxiong; Huang, Xinghua; Huang, Youfeng (Journal of Medical Biochemistry, 2024)
Background: To investigate the effect of percutaneous nephrolithotomy (PCNL) guided by holographic image technology on stress response and renal injury factors in patients with complex renal calculi. Methods: A retrospective analysis was conducted on the clinical data of 70 patients admitted to our hospital between August 2022 and June 2023 who had complex kidney stones. The patients were divided into two groups, namely, group A and group B, based on whether they received guidance from preoperative holographic imaging technology. Group A consisted of forty patients who underwent PCNL after undergoing renal CT examination prior to surgery, while Group B included thirty patients who underwent PCNL guided by holographic imaging technology. Various indexes, including operative factors, stress response, inflammatory response, renal injury factors, renal function, complication rate, and the rate of achieving complete stone clearance in a single procedure, were compared between the two groups. Results: In group B, the puncture time and operation time of the target calyces were shorter compared to group A, additionally, the intraoperative blood loss in group B was lower than that in group A (P<0.05). 24 h after surgery, group B exhibited higher levels of superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) compared to group A, additionally, the level of malondialdehyde (MDA) in group B was lower than that in group A (P<0.05). 24 h after surgery, group B exhibited lower levels of tumor necrosis factor α (TNF-α), interleukin-6 (IL-6), IL-1, and hypersensitive C-reactive protein (hs-CRP) compared to group A (P<0.05). Furthermore, group B showed lower levels of neutrophil gelatinase-associated lipid carrier protein (NGAL), inducible protein-8-like molecule 2 (TIPE2), and β2-microglobulin (β2-MG) than group A at the 7-day mark (P<0.05). 24 h after the operation, There was no statistically significant difference observed in the levels of SCr, BUN, between group A and group Bgroup B(P > 0.05); however, exhibited lower levels of CysC compared to group A (P < 0.05). Additionally, there were no significant differences in postoperative complications between group B and group A (P>0.05). Furthermore, one month after surgery, the one-time stone clearance rate in group B was significantly higher than that in group A (P<0.05). Conclusion: PCNL under the guidance of hologram technology can shorten the time of puncture target calyce and operation, reduce the amount of intraoperative blood loss, effectively reduce the postoperative stress reaction and inflammatory reaction of patients, reduce the level of renal injury factors, improve renal function, and increase the one-time stone clearance rate.